Computation of Vertex Degree-Based Molecular Descriptors of Hydrocarbon Structure - Zeeshan Saleem Mufti; Rukhshanda Anjum; Ayesha Abbas; Shahbaz Ali; Muhammad Afzal; Ashraful Alam (Journal of Chemistry)
Topological indices are such numbers or set of numbers that describe topology of structures. Nearly 400 topological indices are calculated so far. The prognostication of physical, chemical, and biological attributes of organic compounds is an important and still unsolved problem of computational chemistry. Topological index is the tool to predict the physicochemical properties such as boiling point, melting point, density, viscosity, and polarity of organic compounds. In this study, some degree-based molecular descriptors of hydrocarbon structure are calculated.